DAYA TERIMA KONSUMEN PADA PRODUK OLAHAN PANGAN TERSUBSTITUSI TEPUNG BERBASIS SUMBERDAYA LOKAL - Lutfi Aris Sasongko (MEDIAGRO, 2008)
Consume degree of many food processed product decreased because of society purchase decreasing. In economic recovery (2002-2005), rice and corn consume decreased while sweet potato and cassava consume increased. The research was meant to know consumer acceptance on food processed product which substituted with local resource base flour, and to identify proponent and opponent in consume them. The descriptive method was done, with purposive sampling, while selected research area was on Magelang Regent (rural area) and Semarang City (urban area). Sample research design was quota sampling method. The data collections were done with documentation, interview, questioner and product testing. The data analyze used descriptive statistic and Friedman test on significant degree (α = 0.05). The result indicated that consumer acceptance on food processed product which substituted with local resource base flour was good. And it was the key factor of food product diversification acceleration. So  it should be pushed with socialization, demonstration and exhibition. Food processed product diversification acceleration and local resource base flour development should be done to fulfill supply aspect on the market. Keywords : local resource base flour, consumer acceptance